IF YOU WANT TO ARGUE, JUST BEGIN: LINKING MECHANISMS AND THE DISCURSIVE TRADITION IN ACQUISITION - Lopes-Damasio, Lucia Regiane [UNESP] (Univ Estadual Campinas, Inst Estudos Linguagem, 2022)
This study aims to answer the question: What linguistic and discursive evidence can be found in the way linking mechanisms work and the way the argumentative discourse tradition is acquired in the written mode? To do so, it makes an analytical description of the way linking mechanisms operate within a theoretical space that draws on concepts from the discursive tradition (KABATEK, 2005), the heterogeneity of writing (CORREA, 2004), writing acquisition (LEMOS, 1998), and linking mechanisms (RAIBLE, 2001). Sixty texts written by students from pre-school through 4th grade were analyzed using a mixed-methods approach, yielding the following results: (i) description of the functionality of the linking mechanisms in the context in question; (ii) analysis of the symptomatic nature of linking mechanisms as oral/spoken vs. literate/written markers; and (iii) discussion about the relationships between linking mechanisms and acquisition of the argumentative discourse tradition in writing. These results show that transformation and change take place in the symbolic functioning of language through movement and in the subjectification process, which concomitantly affects the tactical forms of language and the meanings established therein.
Keywords: children's writing; junction; discursive tradition